Political legitimacy, fragmentation and the rise of party-formation costs in contemporary Latin America - Scherlis Perel, Gerardo Ezequiel (2014)
This article contributes to the study of party regulation in contemporary Latin America in two main ways. Firstly, it identifies a so far overlooked process by which four countries (Argentina, Colombia, Mexico and Peru) raised party-formation costs in the past decade, an unprecedented process in third-wave Latin American democracies. Secondly, it offers a tentative answer to the question of why this process took place in this specific set of countries. This answer brings to the fore the issues of political parties’ legitimacy and party fragmentation as sources of electoral reform. The article argues that the countries that passed these reforms are those in which the ruling political elites perceived increasing levels of fragmentation as a result of previous reforms that had opened up the political system. These prior reforms were enacted as a response to established parties’ loss of legitimacy. The findings support the more general distinction between reforms initiated due to legitimacy crises and reforms resulting from changing balances of power. In this way the article also contributes to the broader debate on the factors that explain different types of electoral reforms in Latin America.